Diseño de un manual para la prevención de lavado de activos en la Cooperativa de Ahorro y Crédito “Cámara de Comercio” de La Maná. - Guanotuña Tipantuña, Aida Maritza (2020)
Money laundering has fundamental characteristics that allow to understand its origin and the different procedures that illegally carry resources, hence its importance of implementing measures and having tools that allow organizations, specifically credit institutions to detect any irregularities that put at risk. Due to the background described above, it was considered feasible to implement a manual on prevention of money laundering for the Credit Union “Cámara de Comercio” in La Maná; using the documentary, descriptive, explanatory methodology and the analytical, synthetic, deductive methods. Field research was also used to collect information at the credit union’s facilities, bibliographic research for the real support of theoretical information for their analysis, in accordance with the laws established with the regulatory bodies on money laundering. Through the diagnosis of the current state of the institution through the interview and surveys of employees where the rules and control procedures in the prevention of money laundering are not properly applied, due to the absence of guidelines, which could lead to failure to comply with the regulations issued by the UAFE, Therefore, a manual was designed that included policies such as: the responsibilities of the compliance officer, stages, methods, characteristics of money laundering, profile of money laundering, general and internal policies, and penalties for non-compliance, which being properly applied will directly benefit managers, employees, partners and the population of La Mana canton.